Pengembangan Question Card Berbasis PBL untuk Meningkatkan Kemampuan Berpikir Kritis Peserta Didik pada Materi Gerak Lurus - Sutri Widayatun; Thoha Firdaus; Widayanti Widayanti (Pendidikan Fisika Universitas Nurul Huda, 2024)
In 21st-century learning, students must have problem-solving skills, critical thinking, collaboration, and communication intelligence. This research aims to 1) develop PBL-based question cards on straight-motion materials. 2) analyze the improvement of critical thinking skills after applying PBL-based question cards on straight-motion materials. 3) to find out the students' responses to using PBL-based Question Cards on straight-motion materials. This research uses the ADDIE development method. The results of this study obtained the validation value of material experts, which reached an average percentage of 82% with very feasible criteria, in learning using question card learning media, there was an increase in students' critical thinking skills in straight motion materials that were tested using pretest and posttest. The increase that occurred was tested using the N-Gain formula to obtain an average of 0.6 with moderate criteria. The results of the students' responses to the media question card can be said to be very good obtaining an average score of 90%. Based on the results of the data, it can be concluded that PBL-based question card media is feasible and effective to use in straight-motion materials